ANALISIS KARAKTERISTIK PENGUNJUNG DI DEPATI VII COFFEE KOTA SUNGAI PENUH - Volta, Ditop Andra; Putra, Trisna (Ensiklopedia Sosial Review, 2022)
This study originated from the observations of researchers during observations at Depati VII Coffee. Researchers found several problems related to the characteristics of visitors such as the absence of data on the characteristics of visitors visiting Depati VII Coffee. There is no visitor classification data from demographic, geographical and psychographic aspects. The general purpose of this observe changed into to research the characteristics of traffic journeying Depati VII Coffee. The form of studies used on this observe is quantitative with survey methods. In the survey, records become amassed from respondents the use of questionnaires or questionnaires dispensed directly. The variables on this take a look at are self-contained variables which can be characteristics of visitors. The populace on this take a look at had been all visitors who got here to go to Depati VII Coffee with a complete pattern of 100 respondents. The effects of this take a look at were examined for validity and reliability. The information evaluation strategies used are descriptive information with Microsoft excel and SPSS. The effects of the take a look at concluded that almost all of site visitors visited Depati VII Coffee. aged 18 - 24 years as much as 77%, for the sex most obtained by the male gender 55%, for the last education is high school 75%. The type of work obtained from 100 ecutioners distributed to visitors at Depati VII Coffee gets 74% of students/ students, for marital status 86% of visitors are unmarried. Geophysical characteristics of visitors who come to Depati VII Coffee, there are 61% of the area of Sungai Penuh City jambi Province, based on the location where visitors visit Depati VII Coffee there are 95% of visitors living in densely populated housing, for the plains where visitors live 92% come from highland areas around 700 MDPL. Psychographic characteristics of visitors who come to Depati VII Coffee Based on Psychographic Characteristics the majority of visitors with type experiencers with a total of 64% and 36% of visitors with type.